Preparation and characterization of soybean insoluble dietary fiber and its prebiotic effect on dyslipidemia and hepatic steatosis in high fat-fed C57BL/6J mice. Issue 18 (9th August 2021) - Wang, Sainan; Sun, Wanling; Swallah, Mohammed Sharif; Amin, Khalid; Lyu, Bo; Fan, Hongliang; Zhang, Zhao; Yu, Hansong
Abstract : Insoluble dietary fiber extracted from soybean residue had a loose and porous structure, polysaccharide groups, and typical crystalline cellulose I structure. It played a role in regulating lipid metabolism by promoting fatty acid oxidation and inhibiting lipid accumulation. Abstract : The potential benefits of insoluble dietary fiber (IDF) in the regulation of lipid metabolism have been reported in large prospective cohort studies although the molecular regulatory mechanism is still unclear. Okara is a by-product obtained during soybean processing for soy milk and soybean curd (tofu), which is rarely utilized and can be a cheap potential dietary fiber (DF) resource. In this study, the structure and physicochemical properties of insoluble dietary fiber (SIDF) extracted from okara were characterized, and the prebiotic effects on fat metabolism were investigated in vivo . The results showed that the main monosaccharides of SIDF (90.50%) identified were galactose, arabinose, xylose, rhamnose and glucose. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), and X-ray diffraction (XRD) analyses suggested that SIDF had a loose and porous structure, polysaccharide functional groups, and a typical crystalline cellulose I structure. In addition, SIDF had ideal oil-adsorption capacity (OAC; 7.95 g g −1 ) and significantly improved cholesterol adsorption (11.14 mg g −1 ) at pH 7.0. In vivo, IDF supplementation reduced the serum lipid levels and inhibited hepatic fat accumulation. Additionally, SIDF administration improved hepatic steatosis by stimulating lipolysis via upregulation of PPARα, CYP4a10 and CPT1a. This is the first systematic study on the composition, structure, physicochemical properties, adsorption function and biological effects of SIDF. The above results show that SIDF could be used as an ideal functional ingredient in food processing as well as play a positive role in improving the added value of okara and promoting its comprehensive utilization.